Effect of genetics and leaves spraying with arginine and yeast acid on some of the characteristics of Solanum tuberosum L.) - AL-Shamry, Aziz Mahdi Abd; Akram, Zainab Hassan; Khamis, Atheer Abdel Wahab Ali (Journal of agricultural, environmental and veterinary sciences, 2017)
Field experiment was conducted in the hand of the HIBHIB vast area in the Diyala province. During the spring season in 2015 to study Tothiratlath genotypes of potatoes which Emma and Rivira and Loane six transactions of Foliar acid arginine and a yeast; spraying a solution of acid arginine concentration of 200 Melgm.ltr-1, spray a solution of acid arginine concentration of 300 Melgm.ltr1-, spraying a solution of yeast concentration of 5 Gm.ltr-1, spraying a solution of a mixture of acid arginine concentration of 200 Melgm.ltr-1 and yeast solution concentration of 5g. ltr-1. to ratio of 1: 1, spraying a solution of a mixture of acid arginine concentration of 300 Melgm.ltr-1 and yeast solution 5 Gm.ltr-1 1: 1 ratio and the treatment comparison (spraying with distilled water). The experiment carried out in accordance with the system of panels splinters split plot design using RCBD and three replications, tested moral differences between the averages of the traits studied according to Duncan test and the level of probability of 0.05. The study showed superiority installation Rivira highest average weight of the tuber and the weight of the largest tuber and best quotient per plant and the best quotient whole. As for the impact sprinkler transactions plants lost all plants outperformed sprayed on the plants is sprayed and characterized the plants sprayed with a mixture of yeast and acid arginine concentration of 200 Melgm.ltr-1 highest the number of tubers and outperformed the treatment of yeast and acid arginine concentration of 300 Melgm.ltr-1 on the treatment of comparison where gave a higher quotient per plant, and excelled genotype Rivira plants sprayed with yeast and acid arginine 300 Melgm.ltr-1 best number of tubers, as well as genotype Loane sprayed with a mixture of yeast plants acid arginine concentration of 300 Melgm.ltr-1 higher weight to larger tuber, while installation Emma plants sprayed with yeast recorded the highest percentage of dry matter.
Keywords: potatoes; genotypes; yeast; arginine and yield